Occupational exposures to solvents and aluminium and estimated risk of Alzheimer's disease. Issue 9 (September 1998) - Graves, A B; Rosner, D; Echeverria, D; Mortimer, J A; Larson, E B
Abstract : OBJECTIVES: To study the role of occupational exposures to solvents and aluminium in the aetiology of Alzheimer's disease (AD). An industrial hygienist rated exposure. METHODS: 89 subjects diagnosed with probable AD were matched by age, sex, and type of informant to 89 controls. Subjects were identified from a large health maintenance organisation in Seattle, WA. A complete occupational history was obtained from spouses of cases and controls as well as from controls themselves. After the interview an industrial hygienist, blinded to case-control status, rated exposures. RESULTS: Non-significant associations were found between AD and ever having been occupationally exposed to solvents (odds ratio (OR) 1.77, 95% confidence interval (95% CI) 0.81 to 3.90) and aluminium (OR 1.46, 95% CI 0.62 to 3.42). Although an increasing risk was found with increasing number of years of exposure to solvents, there was an inverse association between exposure intensity and AD, and measures of cumulative exposure taking into account both intensity and duration of exposure were not significant. Analysis of the age at which half the cumulative exposure to solvents was achieved showed that an older age incurred a greater risk of AD than a younger age. However, the total amount of exposure carried no risk. CONCLUSIONS: The results suggest that lifetime occupational exposure to solvents and aluminium are not likely to be important risk factors for Alzheimer's disease.